1987
DOI: 10.1097/00005072-198701000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal RNA in Relation to Neuronal Loss and Neurofibrillary Pathology in the Hippocampus in Alzheimer's Disease

Abstract: Topographic analyses were performed on the distribution of neuronal RNA loss in relation to local neuronal loss and neurofibrillary degeneration in the hippocampal region of brains of patients with Alzheimer's disease (AD). Compared to age-matched controls, pyramidal neuronal RNA was depressed (p less than 0.0001) in all areas of the hippocampus examined in AD, viz., the endplate (33%), Rose's H2 field (30%), Rose's H1 field (37%) and the subiculum (46%). Significant neuronal loss was observed in Rose's H1 fie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
14
0

Year Published

1988
1988
1997
1997

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(15 citation statements)
references
References 0 publications
1
14
0
Order By: Relevance
“…If linker histone release from gene regulatory regions is a necessary prerequisite for transcription initiation [22] then an aluminum-mediated enhancement of normal linker histone-DNA binding could be responsible for alterations in template-directed processes such as transcription. This could explain in part the nonrandom reduction of mRNA pool size in Alzheimer afflicted neocortex as measured by quantitative cytophotometric [23] and molecular hybridization techniques [24].…”
Section: Discussionmentioning
confidence: 99%
“…If linker histone release from gene regulatory regions is a necessary prerequisite for transcription initiation [22] then an aluminum-mediated enhancement of normal linker histone-DNA binding could be responsible for alterations in template-directed processes such as transcription. This could explain in part the nonrandom reduction of mRNA pool size in Alzheimer afflicted neocortex as measured by quantitative cytophotometric [23] and molecular hybridization techniques [24].…”
Section: Discussionmentioning
confidence: 99%
“…Hybridization membranes employed in these studies were able to bind RNA fragments as small as 20-25 nucleotides under the conditions used here thereby taking into consideration the effects of PMI on HnRNA or mRNA depolymerization. Importantly, several different laboratories have reported that control, non-Alzheimer dementia and AD affected brains exhibit no statistically significant alterations in the levels of brain ribonuclease activities (Doebler et al, 1987;Guillemette et al, 1987;Maschhoff, White, Jennings & Morrison-Bogorad, 1989), so HNP-L reductions in A D neocortex cannot be attributed directly to HNF-L message instabilities over short PMIs. These data reinforce the concept that the reduced pool size of the HNF-L message in AD is due to a decreased rate of transcription of a particularly stable transcript coding for a neuron specific cytoskeletal message and not to an increase in RNA depolymerization in AD affected brain at postmortem intervals used in these and other studies (Table 2; Clark et al, 1989;Guillemette et al, 1986;Doebler et al, 1987;Crapper McLachlan et al, 1988).…”
Section: Discussjonmentioning
confidence: 99%
“…Importantly, several different laboratories have reported that control, non-Alzheimer dementia and AD affected brains exhibit no statistically significant alterations in the levels of brain ribonuclease activities (Doebler et al, 1987;Guillemette et al, 1987;Maschhoff, White, Jennings & Morrison-Bogorad, 1989), so HNP-L reductions in A D neocortex cannot be attributed directly to HNF-L message instabilities over short PMIs. These data reinforce the concept that the reduced pool size of the HNF-L message in AD is due to a decreased rate of transcription of a particularly stable transcript coding for a neuron specific cytoskeletal message and not to an increase in RNA depolymerization in AD affected brain at postmortem intervals used in these and other studies (Table 2; Clark et al, 1989;Guillemette et al, 1986;Doebler et al, 1987;Crapper McLachlan et al, 1988). Instead, the decrement in RNA signal strength for this important structural component in AD affected human neocortex may be due to the specific occlusion of the RNA polymerase I1 binding site immediately 5' to the HNF-L gene (Lukiw et al, 1990), leading to an impairment of primary transcript generation at this particular neuronal gene locus.…”
Section: Discussjonmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the number of neurons containing tangles in different hippocampal regions does not correlate with the extent of regional RNA loss, azure B RNA staining shows that the total RNA content of hippocampal pyramidal cells is less in AD than in controls (Doebler et al, 1987a). Variable degrees of RNA loss have also been detected in neurons in regions other than hippocampus in AD brain (Doebler et al, 1987b).…”
mentioning
confidence: 97%